Enhanced photodynamic therapy through multienzyme-like MOF for cancer treatment - Lv, Letian; Fu, Zhao; You, Qing; Xiao, Wei; Wang, Huayi; Wang, Chen; Yang, Yanlian (Frontiers in Bioengineering and Biotechnology, 2024)
Overcoming resistance to apoptosis is a major challenge in cancer therapy. Recent research has shown that manipulating mitochondria, the organelles critical for energy metabolism in tumor cells, can increase the effectiveness of photodynamic therapy and trigger apoptosis in tumor cells. However, there is currently insufficient research and effective methods to exploit mitochondrial damage to induce apoptosis in tumor cells and improve the effectiveness of photodynamic therapy. In this study, we present a novel nanomedicine delivery and therapeutic system called PyroFPSH, which utilizes a nanozymes-modified metal-organic framework as a carrier. PyroFPSH exhibits remarkable multienzyme-like activities, including glutathione peroxidase (GPx) and catalase (CAT) mimicry, allowing it to overcome apoptosis resistance, reduce endogenous glutathione levels, and continuously generate reactive oxygen species (ROS). In addition, PyroFPSH can serve as a carrier for the targeted delivery of sulfasalazine, a drug that can induce mitochondrial depolarization in tumor cells, thereby reducing oxygen consumption and energy supply in the mitochondria of tumor cells and weakening resistance to other synergistic treatment approaches. Our experimental results highlight the potential of PyroFPSH as a versatile nanoplatform in cancer treatment. This study expands the biomedical applications of nanomaterials as platforms and enables the integration of various novel therapeutic strategies to synergistically improve tumor therapy. It deepens our understanding of multienzyme-mimicking active nanocarriers and mitochondrial damage through photodynamic therapy. Future research can further explore the potential of PyroFPSH in clinical cancer treatment and improve its drug loading capacity, biocompatibility and targeting specificity. In summary, PyroFPSH represents a promising therapeutic approach that can provide new insights and possibilities for cancer treatment.